Growth, Yield and Quality of Soybean [Glycine max (L.) Merr.] as Influenced by Weed Management and Fertility Levels in Vertisols of S-E Rajasthan - Jadon, Chaman Kumari; Dashora, L. N.; Meena, S. N.; Singh, Pratap (International Journal of Bio-resource and Stress Management, 2019)
A field experiment was conducted at Research Farm, Agricultural Research Station, Kota, Rajasthan during rainy (kharif) season of 2013 and 2014, to evaluate the productivity and quality of soybean as influenced by weed management and fertility levels. The experiment was laid out in split plot design comprising of seven weed management practices in main plot (weedy check, two hand weeding at 20 and 40 DAS, pendimethalin 1.0 kg ha-1 PE+one hand weeding at 30 DAS, imazethapyr 100 g ha-1 at 15 DAS, imazamox+imazethapyr 75 g ha-1 at 15 DAS (ready-mix), clodinafop-propargyl 60 g ha-1 at 15 DAS and quizalofop-ethyl 50 g ha-1 at 15 DAS) and four fertility levels (100% NPK without sulphur, 100% NPK with sulphur, 125% NPK without sulphur and 125% NPK with sulphur) in sub plots with three replications. Pooled results revealed that all the weed management practices and fertility levels were produced significantly higher seed yield and enhanced quality (protein and oil yield) of soybean. Among the herbicidal treatments, post emergence application of ready mix of imazamox+imazethapyr 75 g ha-1 at 15 DAS was produced the highest seed (2013.7 kg ha-1), protein (815.7 kg ha-1) and oil yield of soybean (385.7 kg ha-1) which was significantly superior over clodinafop-propargyl,quizalofop-ethyl and weedy check. Application of 100% NPK (40 N:40 P2O5:40 K2O kg ha-1) along with sulphur (30 kg ha-1) was also found significantly better in terms of yields by giving seed (1736.5 kg ha-1), protein (699.4 kg ha-1) and oil (331.2 kg ha-1) yield of soybean as compared to 100% NPK without sulphur, which was at par with 125% NPK along with sulphur.